The Impact of Nursing Heads Leadership on Research Innovation Behavior of Junior Nurses with Master’s Degree: The Mediation of Perceived Barriers and the Moderation of Motivation - Guo Y; Fan W; Dong X; Yang C; Wang M; Gao H; Lv P; Ma K (Journal of Healthcare Leadership)
Yuanli Guo,1 Wenfeng Fan,2 Xiaofang Dong,1 Caixia Yang,1 Min Wang,3 Huanhuan Gao,3 Peihua Lv,1 Keke Ma1 1Neurology Department, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People’s Republic of China; 2School of Nursing and Health, Zhengzhou University, Zhengzhou, Henan, People’s Republic of China; 3Nursing Department, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People’s Republic of ChinaCorrespondence: Keke Ma, Email 809643627@qq.comBackground: Nursing leadership is recognized as essential to fostering innovation in hospitals, while the precise relationship between them has yet to be established.Aim: The objective of this study is to examine the association among leadership in nursing research, research motivation, perceived barriers, and innovation behavior of junior nurses who hold a master’s degree or above in the hospital.Methods: A cross-sectional survey was conducted and electronic questionnaires were distributed online. An online data analysis tool SPSSAU was adopted to conduct descriptive analysis, correlation analysis, and structural equation model construction. This study adhered to the STROBE guideline.Results: A total of 1025 valid questionnaires were collected in this survey. The leadership in nursing research of head nurses affected nurses’ innovation behavior via perceived barriers. The indirect effect accounted for 59.75% of the total response variance. Research motivation was identified as a moderator in the mediation model, revealing that leadership in nursing research did not significantly affect innovation behavior when nurses showed high motivation.Conclusion: Leadership in nursing research of head nurses and research motivation of junior nurses with master’s degree are crucial to enhancing nursing innovation behavior in the hospitals.Keywords: head nurse, research leadership, research barriers, research motivation